Kinetics and product identification of the reactions of (E) -2-hexenyl acetate and 4-methyl-3-penten-2-one with OH radicals and Cl atoms at 298 K and atmospheric pressure - Gaona Colmán, Elizabeth (2017)
Rate coefficients for the reactions of hydroxyl radicals and chlorine atoms with two biogenic volatile organic compounds as (E)-2-hexenyl acetate and 4-methyl-3-penten-2-one have been determined at 298 K and atmospheric pressure. The decay of the organics was followed using a chromatograph with a flame ionization detector (GC-FID) and the rate constants were determined using a relative rate method. Rate coefficients are found to be (in cm3 molecule-1 s-1): k1(OH + (E)-2-hexenyl acetate) = (6.88 ± 1.41) x 10-11, k2(Cl + (E)-2-hexenyl acetate) = (3.10 ± 1.13) x 10-10, k3(OH + 4-methyl-3-penten-2-one) = (1.02 ± 0.20) x 10-10 and k4(Cl + 4-methyl-3-penten-2-one) = (2.66 ± 0.90) x 10-10 at 298 K. This is the first kinetic experimental study for these reactions studied under atmospheric pressure. The rate coefficients are compared with previous determinations for other unsaturated and oxygenated compounds and reactivity trends are presented. Products identification studies were performed using solid-phase microextraction (SPME) method employing on-fiber products derivatization with o-(2,3,4,5,6-pentafluorobenzyl) hydroxylamine hydrochloride using gas chromatograph with a mass spectrometer detector (GC-MS) for the reactions studied. In addition, atmospheric lifetimes of the unsaturated compounds studied are estimated and compared with other tropospheric sinks for these compounds.